GRAIN BOUNDARY SLIDING IN SUPERPLASTICITY FORMING of TITANIUM ALLOYS (Ti6Al4V) - Armila Armila (Rang Teknik Journal, 2020)
The major property of super plastic material is the high strain rate sensitivity (m ≥ 0.3), which provides high resistance to necking growth, the extension can be obtained is very high (e> 500%) without breaking. decent to obtain high m, the material requirements must have been a fine grain size, where the grain size (d≤ 10µm) is equal-axial or round and stable at high deformation temperatures. Grain boundary sliding is a process in grains slide passing each other, or in the zone directly adjacent to, their common boundary In-situ observation of grain boundary sliding using electron microscopy. The material must be fine-grained, because at super plastic at high temperatures the main deformation mechanism is "Grain Boundary Sliding", Rounded (equal) grain fo where finer grains in the wider plane the sliding plane becomes easier to slide. Large-angle grain boundaries will facilitate sliding. In addition, grain boundaries must be easy to move to avoid local stress concentrations. In super plastic deformation the grain remains equal axial after under large deformation, a proof that grain boundary migration occurs. It should be also pointed out that grain boundary sliding has been considered a dominant deformation mechanism in super plasticity, although the term super plasticity does not simply or even define a particular deformation, mechanism, there is a general agreement that grain boundary sliding contributes more than 50% of the total strain in super plastic material.